Gas Chromatographic Technique Employed for Catalytic Investigation of Novel Phthalocyanines - Sharanakumar, T.M.; Sunilkumar, A.; Somashekar, M.N.; Chethan, B.; Kumar, T. Naveen; Ravikumar, C.R. (Asian Journal of Chemistry, 2023)
The primaquine substituted Fe(II) phthalocyanine (PQFePc) and Co(II) phthalocyanine (PQCoPc) catalysts were prepared by using amide linkage method. The physical and chemical properties have been investigated by FTIR, mass, UV-Vis, TGA, XRD and elemental analysis. The catalytic oxidation of benzyl alcohol was determined by PQFePc and PQCoPc complexes by varying parameters like temperature, oxidant/catalytic ratio and substance/catalyst ratio. The optimization of catalytic oxidation reaction has been effectively achieved for the determination of benzyl alcohol (Bzalc) to benzaldehyde (Bzald). The PQCoPc and PQFePc exhibited excellent catalytic behaviour for the oxidation of benzyl alcohol obtaining high yield and good selectivity.